2016
DOI: 10.3758/s13415-016-0414-7
|View full text |Cite
|
Sign up to set email alerts
|

The neural correlates of happiness: A review of PET and fMRI studies using autobiographical recall methods

Abstract: Although very difficult to define, happiness is becoming a core concept within contemporary psychology and affective neuroscience. In the last two decades, the increased use of neuroimaging techniques has facilitated empirical study of the neural correlates of happiness. This area of research utilizes procedures that induce positive emotion and mood, and autobiographical recall is one of the most widely used and effective approaches. In this article, we review eight positron emission tomography and seven funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 88 publications
1
36
0
1
Order By: Relevance
“…Our findings agree with the results obtained from the previous emotion studies that highlighted the associations of specific neural patterns with different emotions [22], [13], [41]. This is also inline with previous functional magnetic resonance imaging (fMRI) and positron emission tomography (PET) studies, which demonstrated that remembering happy events is primarily associated with the activation of many areas, including anterior cingulate cortex, and prefrontal cortex [42].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings agree with the results obtained from the previous emotion studies that highlighted the associations of specific neural patterns with different emotions [22], [13], [41]. This is also inline with previous functional magnetic resonance imaging (fMRI) and positron emission tomography (PET) studies, which demonstrated that remembering happy events is primarily associated with the activation of many areas, including anterior cingulate cortex, and prefrontal cortex [42].…”
Section: Discussionsupporting
confidence: 92%
“…17,19,20 The increased activity in the ACC, dorsolateral prefrontal cortex, and insula in our study may also be related to invoking emotional memories from the past (since all goals were from previous matches), as it was also shown that remembering emotional events was associated with activation in the ACC, insula, and prefrontal cortex. 21 According to Keenan and coworkers, the right dorsolateral prefrontal cortex is likely to be involved in the memory of information that is personally meaningful. 22 This may explain the co-activation of the right MFG, SFG, and IFG in addition to the dACC in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Most laboratory tasks are motivated by either pleasure or pain and as such are endowed with motivational valence. Human imaging studies have shown that the medial frontal cortex (MFC) including the anterior cingulate cortex (ACC) is activated during the experience of pain, fear and sadness (Peterson, 1986 ; Kulkarni et al, 2005 ; Wiech and Tracey, 2009 ; Etkin et al, 2011 ; Shackman et al, 2011 ; Yoshino et al, 2013 ; Palermo et al, 2015 ; Wagner et al, 2015 ; Fullana et al, 2016 ) as well as by the experience of pleasure or happiness (Rolls et al, 2003 ; Lindgren et al, 2012 ; Matsunaga et al, 2016 ; Suardi et al, 2016 ). At the cellular level, MFC/ACC neurons respond robustly to cues that predict aversive outcomes.…”
Section: Introductionmentioning
confidence: 99%